Mothers’ Life-Worlds in a Developing Context when a Child has Special Needs - Hemming, Eve (The Indo-Pacific journal of phenomenology, 2009)
This South African study investigates the lived experiences of a group of isiZulu mothers of children diagnosed with multiple disabilities. Data collection from regular focus group discussions proceeded with the assistance of a translator skilled in working in isiZulu and English. The phenomenological approach employed revealed the mothers’ philosophical acceptance of their child’s disability. Issues of concern to the women that emerged include the effects of the child’s disability on their lives, the treatment options for their children, and their perceptions of the causes of the disability. The women reflect on both traditional and Western treatment options and articulate the constraints they experience as caregivers, with limited childcare facilities preventing them from finding employment, difficulties in accessing social service grants exacerbating their position, and various levels of family and community support experienced. The study underlines the need for more adequate service provision for children with special needs and their families, and for intervention programmes to be informed by an understanding of the contexts and ways of making meaning of those whose needs they are intended to serve.